Intersections of voice and agency as strategies for power and resistance in the poetry of Maya Angelou - Kaberia, Teresia (Hybrid Journal of Literary and Cultural Studies, 2021)
This article sought to analyse intersections of voice and agency in the poetry of Maya Angelou. It explores how various discourses of marginalization such as those of gender, race and class inform knowledge production by marginalized persons as portrayed in Angelou’s poetry. The article demonstrates how the marginalized appropriate voice to resist hegemony. This is validated through voice reclamation and performative subjectivity to articulate issues of the marginalized as one way of resisting hegemonic discourses that have governed their parameters for agency and identity. The data for analysis in this article is obtained from a critical reading and sampling of poems in The Complete Collected Poems of Maya Angelou. Anchored on the intersectionality theory, the article examines Angelou’s representation of the Spivakian concept of voice as appropriated by the marginalized and how in its intersection with agency, is used as a rhetoric of resistance in her poetry.
Keywords: Agency; Empowerment; Intersection; Resistance; Voice